A Novel Image Encryption Algorithm Based on Chaotic Sequences and Cross-Diffusion of Bits - Geng Shengtao; Wu Tao; Wang Shida; Zhang Xuncai; Niu Ying (IEEE Photonics Journal)
To protect image information security, we propose an encryption algorithm based on chaotic sequences and bits' cross-diffusion. First, two chaotic sequences are generated by two-dimensional logic-sine coupling mapping, and the original image is scrambled with the two sequences. Secondly, the scrambled image is transformed into a one-dimensional sequence, and the low-order bits between every two pixels are fused to change the detailed information of the image, improved the ability to resist differential attacks. Finally, chaotic sequences are generated by iterative logical mapping to perform pixel replacement and ciphertext diffusion. The known plaintext attack can be effectively resisted because of the stochastic combination of diffusion scheme and chaotic sequence. It also has a significant effect on resisting differential attack. Take Lena image as an example, NPCR and UACI can reach 99.6063% and 33.4477%, respectively, which are very close to the ideal value. The encryption scheme has good key sensitivity and strong ability to resist statistical attacks, which shows that the algorithm has adequate security.